Legal status of professional staff of the constitutional court of the Republic of Kazakhstan (VERITAS LEGIS JOURNAL, 2025)
Abstract. This article examines the role and significance of the professional staff of the Constitutional Court of the Republic of Kazakhstan, who, despite lacking a special constitutional status as judges, play a key role in ensuring the full and effective functioning of this constitutional oversight body. The article considers their legal status, as well as the structure and functions of the apparatus of the Constitutional Court of the Republic of Kazakhstan, including its analytical, organizational-legal, and expert divisions. Special attention is given to the characterization of auxiliary personnel—consultants, specialists (analysts), and other staff members responsible for preparing case materials, conducting legal research, organizing document flow, coordinating with other state bodies, and implementing the decisions of the Constitutional Court. The article highlights the features of the Kazakhstani model in comparison with foreign experience, including the legislative practices of the Russian Federation and Poland, with supporting reasoning. The author emphasizes that the effectiveness of the Constitutional Court’s activities largely depends on the high level of professional training, experience, and responsibility of its staff. In conclusion, recommendations are proposed to strengthen the legal regulation of their activities, enhance transparency, and reinforce the institutional significance of these «persons without robes» in constitutional justice.
Keywords: Constitutional Court, legal status, apparatus, auxiliary bodies, staff, analyst, constitutional justice